An antisense noncoding RNA enhances translation via localized structural rearrangements of its cognate mRNA. Issue 4 (25th January 2021) - Reis, Rodrigo S; Deforges, Jules; Schmidt, Romy R; Schippers, Jos H M; Poirier, Yves
Abstract: A large portion of eukaryotic genes are associated with noncoding, natural antisense transcripts (NATs). Despite sharing extensive sequence complementarity with their sense mRNAs, mRNA–NAT pairs elusively often evade dsRNA-cleavage and siRNA-triggered silencing. More surprisingly, some NATs enhance translation of their sense mRNAs by yet unknown mechanism(s). Here, we show that translation enhancement of the rice ( Oryza sativa ) PHOSPHATE1.2 ( PHO1.2) mRNA is enabled by specific structural rearrangements guided by its noncoding antisense RNA ( cis -NATpho1.2 ). Their interaction in vitro revealed no evidence of widespread intermolecular dsRNA formation, but rather specific local changes in nucleotide base pairing, leading to higher flexibility of PHO1.2 mRNA at a key high guanine-cytosine(GC) regulatory region inhibiting translation, ∼350-nt downstream of the start codon. Sense–antisense RNA interaction increased formation of the 80S complex in PHO1.2, possibly by inducing structural rearrangement within this inhibitory region, thus making this mRNA more accessible to 60S. This work presents a framework for nucleotide resolution studies of functional mRNA–antisense pairs. Abstract : Interaction between PHO1.2 mRNA and its cis -natural antisense transcript enhances translation via a mechanism involving a local conformational shift and disruption of a key inhibitory region.